Lifestyle Modifications to Help Prevent Headache at a Developmental Age - Raucci, Umberto; Boni, Alessandra; Evangelisti, Melania; Della Vecchia, Nicoletta; Velardi, Margherita; Ursitti, Fabiana; Terrin, Gianluca; Di Nardo, Giovanni; Reale, Antonino; Villani, Alberto; Parisi, Pasquale (Frontiers in Neurology, 2021)
Headache is the world's seventh most significant cause of disability-adjusted-life in people aged between 10 and 14 years. Therapeutic management is based on pharmacological approaches and lifestyle recommendations. Many studies show associations between each migraine-promoting lifestyle, behavioral triggers, frequency, and intensity of headaches. Nevertheless, the overall aspects of this topic lack any definitive evidence. Educational programs advise that pediatric patients who suffer from migraines follow a correct lifestyle and that this is of the utmost importance in childhood, as it will improve quality of life and assist adult patients in avoiding headache chronicity, increasing general well-being. These data are important due to the scarcity of scientific evidence on drug therapy for prophylaxis during the developmental age. The “lifestyle recommendations” described in the literature include a perfect balance between regular sleep and meal, adequate hydration, limited consumption of caffeine, tobacco, and alcohol, regular physical activity to avoid being overweight as well as any other elements causing stress. The ketogenic diet is a possible new therapeutic strategy for the control of headache in adults, however, the possible role of dietary factors requires more specific studies among children and adolescents. Educational programs advise that the improvement of lifestyle as a central element in the management of pediatric headache will be of particular importance in the future to improve the quality of life of these patients and reduce the severity of cephalalgic episodes and increase their well-being in adulthood. The present review highlights how changes in different aspects of daily life may determine significant improvements in the management of headaches in people of developmental age.